KONTEKSTUALISASI MAKNA JIHAD DI ERA MILENIAL - Dwi Hartini (IAIN Ponorogo, 2019)
Abstract: It has already believed that Jihad has recently become an issue to be debated in East and West. However, the concept of jihad is misinterpreted narrowly as he activities dealing with warfare and murder. Jihad in broader sense can be defined as the efforts to support the religion of Allah SWT. This paper is intended to highlight several verses and hadith from the Prophet concerning the jihad concept. It is essential to be done in order to prove that jihad in Islam is not only conquest of the city, seizing property and Islamizing city residents, but also jihad in the Islamic state has a function in supporting Allah and the liberation of humans from the life of